Need of Point of Care Ultrasound Training in Pediatric Emergency Medicine Practice: A Wake-Up Call for the Low-Income Countries - Noman Ali MBBS, FCPS (EM); Erum Shakeel MBBS; Salman Muhammad Soomar MSc (SAGE Publishing, 2023)
POCUS is the acquisition, interpretation, and rapid clinical integration of ultrasonographic imaging performed by the treating physician at the patient's bedside. It is used in the field Emergency Medicine to assist in diagnosing and managing various clinical conditions ranging from undifferentiated shock, respiratory failure, and cardiac arrest, which have shown a positive impact on clinical decision-making, resulting in a decreased emergency department and hospital length of stay. POCUS is also a valuable diagnostic tool in managing pediatric patients for whom radiation exposure is a significant concern. It is used to aid in diagnosing and managing various pediatric medical and surgical emergencies. Despite the evident literature regarding the utility of POCUS in Pediatric Emergency Medicine (PEM) practice, there is a lack of specialized training for pediatric emergency physicians, especially in low-income countries. Therefore, this comment emphasizes the need for POCUS training in PEM.